Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1108/qmr-07-2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

Market-mediated authenticity in culturally themed culinary space

Abstract: Purpose This paper aims to explore authenticity as a multidimensional construct from both consumer and service provider perspectives in the context of culturally themed restaurants in Kolkata, India. Design/methodology/approach Utilizing a phenomenological design, data have been collected through participant observation, photographs and semi-structured interviews in Bengali-themed restaurants over a two-year period. Findings By articulating the processes and dimensions that operate behind the narrative of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
0
8
0
2
Order By: Relevance
“…Thus, a brand with a long history is associated with characteristics such as being credible, trustworthy, familiar, secure, and reliable (Chang and Tung, 2016). Furthermore, researchers have suggested that restaurants' history significantly affects customers' perceived restaurant authenticity (Sinha et al, 2018). Accordingly, the authenticity of traditional cuisine is often portrayed by the stereotypical image originating in the "good old days" (Scarpato and Daniele, 2003).…”
Section: Role Of the History Of A Restaurantmentioning
confidence: 99%
“…Thus, a brand with a long history is associated with characteristics such as being credible, trustworthy, familiar, secure, and reliable (Chang and Tung, 2016). Furthermore, researchers have suggested that restaurants' history significantly affects customers' perceived restaurant authenticity (Sinha et al, 2018). Accordingly, the authenticity of traditional cuisine is often portrayed by the stereotypical image originating in the "good old days" (Scarpato and Daniele, 2003).…”
Section: Role Of the History Of A Restaurantmentioning
confidence: 99%
“…Despite such progress, there remains little understanding of important mediators, such as perceived authenticity and nostalgic experiences, in the brand heritage model. Researchers have suggested that heritage enhances individuals' authenticity perceptions (Gundlach & Neville, 2012;Sinha et al, 2018) and evokes nostalgia (Pecot et al, 2019). They have further noted that both brand authenticity (Beverland, 2009;Gundlach & Neville, 2012) and nostalgia (Marchegiani & Phau, 2010;Zhou et al, 2019) influence consumers' purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…They influence the weighted involvement of TV actors in the TV and the development of thematic villages. The fact that the modern user is Experience-oriented is confirmed by the authors who analyzed the thematic objects, who state that theming is one of the main methods for creating opportunities for the use of experiences, which are especially sought after by modern users (Pine, Gilmore, 2011; Stromberg, 2015; Astrom, 2017; Wong, Cheung, 1999; Sinha et al, 2018). Village theming provides opportunities for modern users to find the experiences they are looking for.…”
Section: Discussionmentioning
confidence: 99%